EFFICIENCY ANALYSIS OF OFF-SEASON CAPSICUM/BELL PEPPER PRODUCTION IN PUNJAB-PAKISTAN: A DEA APPROACH - Q. Ali; M. T. I. Khan; M. Ashfaq (Journal of Animal and Plant Sciences, 2018)
The aim of present study was the estimation of technical, allocative and economic efficiency and inefficiency determinants in off-season capsicum/bell pepper production in Punjab, Pakistan. Primary data were collected from 70 off-season capsicum/bell pepper growers by simple random sampling in 2014. Data Envelopment Analysis Procedure revealed that mean technical efficiency was higher (78.8%) followed by allocative ( 56.6%) and economic efficiencies (44.3%) . It indicates the possibility of 21.2% decrease in inputs and 43.4% decrease in total cost for technically and allocatively efficient farmers while output and technology remained unchanged. The lowest value of technical (40.8%), allocative ( 17.2%) and economic (17.2%) efficiencies were also calculated. Small farmers show high technical ( 89.0%), allocative (70.2%) and economic ( 62.5%) efficiencies. Tobit model shows that the education, experience in off-season capsicum/bell pepper production and meetings with extension staff had a significant and negative impact on inefficiency. The effect of family size, off-season capsicum/bell pepper area and distance of vegetable market was significant and positive on inefficiency. The government should improve the level of education, technical knowledge, extension services and quality of inputs. The government should provide a subsidy to small farmers in the purchase of tunnel material. was Rs. 66531.3 million in 2015-16 (Government of
Keywords: Production efficiency; Farm size; Tunnel farming; Tobit Model; Off-season pepper.